Low‐grade intraductal carcinoma of the salivary gland with prominent oncocytic change: a newly described variant. Issue 2 (21st May 2018) - Nakaguro, Masato; Urano, Makoto; Suzuki, Hiroaki; Yamada, Kazuyuki; Sakaguchi, Asumi; Ogura, Kanako; Matsumoto, Toshiharu; Ono, Noritsugu; Asato, Tsuguharu; Mikami, Yoshiki; Imai, Hiroshi; Nagao, Toshitaka
Abstract : Aims: Low‐grade intraductal carcinoma (LG‐IDC) is a clinically indolent malignant tumour of the salivary glands. Because of its rarity, the histological variants of LG‐IDC have not been well characterised. Herein, we describe five LG‐IDC cases with prominent oncocytic change in the major salivary glands. Methods and results: We examined five cases, three males and two females (mean age = 63 years), of LG‐IDC with oncocytic change. The sites affected by LG‐IDC were the parotid and submandibular glands. The lesions were macroscopically unilocular or multilocular cysts with a solid tumour arising from the cyst wall. Smaller tumour cell nests were also observed. As with classic LG‐IDC, the cyst wall was surrounded by myoepithelial cells with no invasive component. The tumour cells had abundant oncocytic cytoplasm and proliferated in a low‐papillary, tubular or cribriform pattern. Immunohistochemically, the tumour cells were diffusely positive for pan‐cytokeratin, S100, mammaglobin and antimitochondria antibody, and were negative for androgen receptor and gross cystic disease fluid protein‐15. Unlike classic LG‐IDC, some of these cases demonstrated focal invagination of myoepithelial cells in the intraductal tumour. Conclusion: Oncocytic LG‐IDC should be recognised as a histologically unique variant of LG‐IDC. Awareness of this entity is important to avoid erroneous diagnosis and inappropriate treatment for histological mimics.